Primary health care indicators' profile in the state of São Paulo: 10-year retrospective - Sala, Arnaldo; Mendes, José Dínio Vaz (Saúde e Sociedade, 2011)
More than 20 years after the creation of Sistema Único de Saúde (SUS - Brazil's National Health System) and after a long period of improvements in primary health care (PHC) in the State of São Paulo, Brazil, one of the most important tasks is to evaluate their processes and their health outcomes. The aim of this study is to analyze the profile of indicators related to PHC in the State of São Paulo during the last decade (2000 to 2009). Fourteen indicators related to PHC structure, SUS performance and to health conditions were selected. These indicators were analyzed considering the entire State of São Paulo and by groups of municipalities defined by their population (small: less than 20 thousand inhabitants; medium: between 20 and 100 thousand inhabitants; large: more than 100 thousand inhabitants) and by their wealth (low; high). Almost all the 14 selected indicators improved along the period. The PHC structure-related indicators had a global improvement, and the groups of small municipalities showed better levels along the entire period. The SUS performance-related indicators showed differences among groups of municipalities. The group of large municipalities obtained lower hospitalization rates in conditions preventable by PHC. Nevertheless, this same group had the lowest rates of pap smear tests. The group of small and high wealth municipalities presented better trends in health condition indicators. The group of large municipalities presented the highest rates of mortality caused by cervical cancer and cardiovascular disease. In conclusion, there is a clear improvement in PHC in terms of structure, health care performance and health conditions.